Banana and plantain-based foods consumption by children and mothers in Cameroon and Southern Nigeria: A comparative study - Honfo, Gbenato Fernande (My University, 2011)
Bananas and plantains (Musa spp.) play an important role in the diet of people in Central and West Africa. In Cameroon and Southern Nigeria, a comparative study was carried out in 480 households to assess the frequencies and levels of consumption of banana and plantain-based foods commonly consumed by children under five years-old and their mothers. The results revealed some degree of similarities in the areas of boiled, roasted and fried banana or plantain between the two countries. Consumption frequencies of banana and plantain-based foods and consumption levels were higher among the respondents in Cameroon compared to Southern Nigeria surveyed. The daily consumption levels of boiled plantain, fried plantain and ripe banana were 225, 136 and 145 g respectively for children from Cameroon, while in Nigeria, the figure were 112, 82 and 80 g respectively. The daily consumption levels of the same recipes among the Cameroonian mothers were 402, 300 and 304 g respectively whereas among the Nigerian mothers, there were 265, 158 and 165 g. The study showed that banana and plantain-derived food were more consumed in Cameroon than in Southern Nigeria.
Keywords: Musa spp.; plantain-based foods; consumption frequency; level of consumption